1987
DOI: 10.1042/bj2460537
|View full text |Cite
|
Sign up to set email alerts
|

Active-site- and substrate-specificity of Thermoanaerobium Tok6-B1 pullulanase

Abstract: Thermoanaerobium Tok6-B1 pullulanase (EC 3.2.1.41) was active on alpha 1-6-glucosidic linkages of pullulan, amylopectin and glycogen and the alpha 1-4 linkages of amylose, amylopectin and glycogen but not of pullulan. Hydrolysis of short-chain-length malto-oligosaccharides (seven or fewer glucose residues) yielded maltose as product. Pullulan hydrolysis was pH-dependent and a plot of log(V/Km) versus pH implied a carboxy group with pKa 4.3 at the active site. Modification with 1-(3-dimethylaminopropyl)-3-ethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Recently, some enzymes that demonstrate dual specificity towards a-(1-.4)-and a-Q-1-6)-glucosidic linkages have been reported (3,10,12). Thermoanaerobium sp.…”
Section: -O-a-(63-o-a-glucosyl-maltotriosyl)-maltose As An Exam-mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some enzymes that demonstrate dual specificity towards a-(1-.4)-and a-Q-1-6)-glucosidic linkages have been reported (3,10,12). Thermoanaerobium sp.…”
Section: -O-a-(63-o-a-glucosyl-maltotriosyl)-maltose As An Exam-mentioning
confidence: 99%
“…Thermoanaerobium sp. strain Tok6-B1 puliulanase (10) and Thermoanaerobium brockii debranching enzyme (3) can cleave the a-(i--*6) linkages [and none of the a-(l-*4) bonds] of pullulan and the a-(1-4) linkages of starch. On the other hand, Thermoactinomyces vulgaris a-amylase attacks some of the a-(1-.6) linkages in partial hydrolysates ofpullulan as well as a-(1-34) linkages in starch and puliulan (12) (3 3 clearly distinguished from a-amylase.…”
Section: -O-a-(63-o-a-glucosyl-maltotriosyl)-maltose As An Exam-mentioning
confidence: 99%
“…Recently, other pullulan-hydrolyzing enzymes that hydrolyze both a-(1->4)-and a-(1--+6)-glucosidic linkages have been reported (2,15,16). Melasniemi et al (11) reported that the primary structure of the a-amylase-pullulanase from Clostridium thermohydrosulfuricum closely resembled that of neopullulanase.…”
mentioning
confidence: 99%
“…On the other hand, Plant et al (15) suggested that the same active center participated in the dual activity toward a-(1-->4)-and a-(1-*6)-glucosidic linkages, as indicated by * Corresponding author. studies of chemical modification and enzymatic kinetics of Thermoanaerobium sp.…”
mentioning
confidence: 99%
“…The protein encoded by the pul gene has putative N-terminal pullulanase and C-terminal alpha-amylase domains, potentially able to act on pullulan, amylopectin, or glycogen (20,35). The pul gene lies directly upstream from the glg operon, suggesting that the encoded protein might be involved in determining IPS branch structure and/or IPS metabolism.…”
Section: Discussionmentioning
confidence: 99%